2004
DOI: 10.1121/1.1736654
|View full text |Cite
|
Sign up to set email alerts
|

Active control of radiation from a piston set in a rigid sphere

Abstract: Active control of the sound radiated from a piston set in a rigid sphere with a set of control point sources around is considered in this paper, where the scattering sound field of the control sound from the rigid sphere has been taken into account to minimize the total radiated sound power. Analytic results of the sound power are obtained and numerical simulations show that it is possible to reduce the radiation from a small piston set in a rigid sphere similar to the size of a human head up to a certain freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…where j ¼ (À1) 1/2 , p 0 is the amplitude of the incident wave, k is the wave number, j l (Á) is the spherical Bessel function of order l, and P l (Á) is the Legendre function of order l. The total sound field with consideration of the rigid sphere scattering can be expressed as 21,22…”
Section: A Far-field Sound Source Model With a Scatterermentioning
confidence: 99%
See 2 more Smart Citations
“…where j ¼ (À1) 1/2 , p 0 is the amplitude of the incident wave, k is the wave number, j l (Á) is the spherical Bessel function of order l, and P l (Á) is the Legendre function of order l. The total sound field with consideration of the rigid sphere scattering can be expressed as 21,22…”
Section: A Far-field Sound Source Model With a Scatterermentioning
confidence: 99%
“…The superscript (*) denotes complex conjugation. The total sound field with consideration of the rigid sphere scattering can be expressed as 21,22 FIG. 1.…”
Section: B Point Source Model With a Scatterermentioning
confidence: 99%
See 1 more Smart Citation
“…Since a practical VSB system has to be implemented surrounding a person, at least a human's head, the effect of such a diffracting body on the performance of the VSB system must be considered. Active control of the sound radiated from a piston set in a rigid sphere with a set of control point sources around was studied by Lin et al, where the scattering sound field of the control sound from the rigid sphere has been taken into account to minimize the total radiated sound power [4]. It has been shown that due to the scattering effect of the rigid sphere, the presence of the rigid sphere is beneficial for the active control.…”
Section: Introductionmentioning
confidence: 99%
“…When a rigid sphere is put near a single channel ANC system, the rigid sphere has scattering effects on both the primary and secondary fields and can increase global sound radiation control performance after optimizing the locations of secondary sources; however, no detailed mechanism was investigated [9]. It was also discovered that the presence of a human head in a three dimensional virtual sound barrier system can improve or decrease the system performance depending on the size of the quiet zone surrounded by the error sensors and the noise frequency [10].…”
Section: Introductionmentioning
confidence: 99%